Procalcitonin-Guided Antibiotic Therapy in Patients with Lower Respiratory Tract Infections - Butterman, Eric (MD Conference Express, 2011)
This article discusses data from a quality control survey [ISRCTN40854211] that monitored procalcitonin (PCT)-guided antibiotic therapy and algorithm adherence in simulated “real-life” conditions. The integration of the PCT algorithm into daily practice requires ongoing reinforcement and involves a learning process by prescribing physicians [Schuetz P et al. Eur J Clin Microbiol Infect Dis 2010].